Study of the Mechanical Properties of Nano Silver Nitrate Filled Polypropylene Composites. Issue 1 (12th June 2018) - Ozel, Ahmet; Unal, Huseyin; Mimaroglu, Abdullah
Abstract : In this investigation, the mechanical properties of silver nitrate nanoparticles filled polypropylene composite is evaluated. The silver nitrate particles are added to the matrix by 1, 3, 5, and 10% by weight. The composite is prepared by adding the filler to polypropylene under heat and mix the mixture by mechanical stirrer. Then after the test samples are prepared under hot press. The tensile tests are carried out. The tensile strength, yield stress, tensile modulus, and the percentage of elongation to break are obtained and evaluated. The results show that the elastic modulus of the composite is in increase while tensile strength, rupture strength, and the percentage of elongation to break is in decrease with the increase in the content of silver nitrate particle fillers. The morphology, structure, and size of the silver nitrate particles are evaluated by scanning electron microscope.